LITERATURE REVIEW: THE EFFECT OF COMPENSATION ON EMPLOYEE PERFORMANCE - Amanda Puspaningrum Sulistyorini; Yerizal (Journal Informatic, Education and Management (JIEM), 2026)
Globalization and technological progress have encouraged organizations to manage human resources more effectively in order to maintain competitiveness. Compensation is one of the essential components of human resource management and is often considered a factor that can improve employee performance. This study aims to examine the effect of compensation on employee performance and to identify other variables that influence performance. A systematic literature review method was employed by analyzing 15 previous studies published between 2015 and 2025 that discuss the relationship between compensation and employee performance. The results are presented through tables and supported by descriptive and comparative analysis. The findings indicate that compensation generally has a positive influence on employee performance, although the level of impact varies. Several studies report a strong effect, with compensation contributing more than 70% to performance, while others show a moderate effect ranging from 40% to 70%, and some indicate a low influence below 40%. In certain cases, compensation shows no significant or even negative effect on performance. In addition to compensation, factors such as motivation, leadership style, work discipline, work environment, organizational culture and job satisfaction are also found to significantly affect employee performance.